Washington State Surgeon Perspectives on Quality Measures in the Surgical Care of Stress Urinary Incontinence in Women. Issue 1 (19th January 2021) - Adelstein, Sarah A.; Du, Chris; Berry, Donna L.; Gore, John L.; Fialkow, Michael F.; Lee, Una J.
Abstract: Introduction: No consensus exists on outcomes that define high quality care in female stress urinary incontinence management. A working group of surgeons from diverse health care settings in Washington State who treat stress urinary incontinence was convened through a state level quality collaborative. Preliminary questions were developed and focus groups conducted to obtain surgeon input and perspectives on stress urinary incontinence surgery quality measures to guide future research. Methods: Washington State surgeons who perform sling surgery were recruited via email. Focus groups were convened via teleconference using preliminary questions as discussion points. Participants were surgeons from a variety of locations and practice types. Focus groups were led by a trained moderator, recorded and transcribed verbatim, and qualitatively analyzed using inductive content analysis. Results: Eight urologists and 6 gynecologists from 5 academic, 4 private practice and 5 hospital based settings participated in 3 focus groups. The 4 emergent concepts derived, were a perceived need to individualize rather than standardize the management approach to recurrent and persistent stress urinary incontinence, a need to establish and validate shared decision making tools for synthetic mesh procedures, a need to define risk factors and treatment strategies for unique populations, including those with mixed urinary incontinence, younger patients and those with concomitant prolapse, and an enthusiasm to identify practical and clinically meaningful quality measures. Conclusions: Focus groups with clinical experts on quality of stress urinary incontinence care identified several priority topics for future study. Further work is needed to refine research prioritization on this important area of women's health.